Pengaruh Terapi Relaksasi Lima Jari dan Senam Hamil Terhadap Kecemasan pada Kehamilan Trimester 3 Menjelang Persalinan di PMB Ny. M di Kabupaten Cianjur Tahun 2024 - Butet Agnes Melani Sinaga; Retno Sugesti (Pusat Riset dan Inovasi Nasional, 2025)
The third trimester of pregnancy, especially towards delivery, is a crucial phase for expecting mothers. Anxiety during this period is a common emotional response, which can affect both maternal and fetal health. This study aims to assess the effects of relaxation therapy using the